Forrest Gump - Groom, Winston 1944-; Zemeckis, Robert 1952-; Roth, Eric; Finnerman, Wendy; Tisch, Steve (Paramount, 1994)
Through three turbulent decades, Forrest rides a tide of events that whisks him from physical disability to football stardom, from Vietnam hero to shrimp tycoon, from White House honors to the arms of his one true love.